2013
DOI: 10.1111/gfs.12082
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyphenol oxidase activity in a range of forage ecotypes with different phenol substrates. A new insight for PPO and protein‐bound phenol evaluation

Abstract: Plant phenols can influence utilization of forages by ruminants through binding with proteins either by complexing with oxidized phenols (products of polyphenol oxidase activity or formed in oxidizing conditions) or by hydrogen binding with tannins. These protein-bound phenols (PBPs) affect rumen metabolism by inhibition of both proteolysis and lipolysis. The aim of this work was to assess the level of polyphenol oxidase (PPO) activity (determined with a range of diphenolic substrates), PBP content, and to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…However, the epiphytic lactic acid bacteria biomass on the surface of all forages were found to be adequate, exceeding the satisfactory level 5 log 10 CFU/g FW (Silva et al., ). The PPO activity detected in red clover was within the range established in previous reports (Cabiddu et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…However, the epiphytic lactic acid bacteria biomass on the surface of all forages were found to be adequate, exceeding the satisfactory level 5 log 10 CFU/g FW (Silva et al., ). The PPO activity detected in red clover was within the range established in previous reports (Cabiddu et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…For this reason, it is necessary to understand the interactions of UFA, PPO, coronaric acid and others PSM and clarify the role of each component on the ruminal biohydrogenation pathways. Preliminary results from Cabiddu et al (2011) showed that plant PPO activity could be affected by specific tannins with an interaction of forage species and plantphenological stage (Fig. 19).…”
Section: Interaction Between Ppo Psm Endogenous Lipolysis and Pufamentioning
confidence: 99%
“…When the PPO enzyme from red clover was incubated with a wide range of ortho-diphenols in the presence of oxygen, there was rapid conversion from the latent to the active form of PPO (Lee et al, 2008a), a conversion inhibited by adding ascorbic acid, suggesting that this mechanism requires formation of ortho-quinones. Other factors which influence the efficacy of PPO, to produce phenol-bound protein and/or PPO activation includes oxygen concentration, the phenological stage of the plant and the plant's NDF content (Lee et al, 2009b;Cabiddu et al, 2011).…”
Section: Plant Endogenous Factors Which Influence Fatty Acid Profilementioning
confidence: 99%
“…The levels of TotP, NTP and TP in tagasaste leaves were 3 to 6 times higher than values found in a range of Mediterranean annual grass, legume and herb species such as Lolium rigidum Gaud., Medicago polymorpha L., Medicago arabica L., Plantago lanceolata L., Trifolium cherleri L. and T. resupinatum L. (Cabiddu et al, 2013). The levels of TotP, NTP found in Mediterranean populations of forage chicory (Piluzza et al, 2014) were half than those reported for tagasaste.…”
Section: Discussionmentioning
confidence: 76%